Hyperoxia but not AOX expression mitigates pathological cardiac remodeling in a mouse model of inflammatory cardiomyopathy - Dhandapani, Praveen K.; Begines-Moreno, Isabel M.; Brea-Calvo, Gloria; Gärtner, Ulrich; Graeber, Thomas G.; Sanchez, Gerardo Javier; Morty, Rory E.; Schönig, Kai; Hoeve, Johanna ten; Wietelmann, Astrid; Braun, Thomas; Jacobs, Howard T.; et al. (Scientific reports, 2019)
Constitutive expression of the chemokine Mcp1 in mouse cardiomyocytes creates a model of inflammatory cardiomyopathy, with death from heart failure at age 7-8 months. A critical pathogenic role has previously been proposed for induced oxidative stress, involving NADPH oxidase activation. To test this idea, we exposed the mice to elevated oxygen levels. Against expectation, this prevented, rather than accelerated, the ultrastructural and functional signs of heart failure. This result suggests that the immune signaling initiated by Mcp1 leads instead to the inhibition of cellular oxygen usage, for which mitochondrial respiration is an obvious target. To address this hypothesis, we combined the Mcp1 model with xenotopic expression of the alternative oxidase (AOX), which provides a sink for electrons blocked from passage to oxygen via respiratory complexes III and IV. Ubiquitous AOX expression provided only a minor delay to cardiac functional deterioration and did not prevent the induction of markers of cardiac and metabolic remodeling considered a hallmark of the model. Moreover, cardiomyocyte-specific AOX expression resulted in exacerbation of Mcp1-induced heart failure, and failed to rescue a second cardiomyopathy model directly involving loss of cIV. Our findings imply that mitochondrial involvement in the pathology of inflammatory cardiomyopathy is multifaceted and complex.